A history of pan-African revolt - James, C. L. R (Oakland PM Press, 2012)
Originally published in England in 1938 and expanded in 1969, this work remains the classic account of global Black resistance. This concise, accessible history of revolts by African peoples worldwide explores the wide range of methods used by Africans to resist oppression and the negative effects of imperialism and colonization as viewed in the 20th century. Written from a radical perspective with a substantial new introduction that contextualizes the work in the ferment of the times, A History of Pan-African Revolt is essential to understanding liberation movements in Africa and the diaspora and continues to reveal new insights, lessons, and visions to successive generations.
Originally issued in England in 1938 and expanded in 1969.
Keywords: Pan-Africanism --History.